Cement stabilized soils : strength behaviour / Muhammad Iswandy Bujang Hadi - Bujang Hadi, Muhammad Iswandy (1998)
The project aims at finding the effect of ratio of soil-cement on the basic properties and strength behavior of weak soil (soft clay or peat soil) such as plasticity, permeability, etc. Very often soil improvement techniques are adopted in the area of the soil where the problems pursuing development on soft clay soil is well known. The project examines engineering properties and strength behaviour of the soil samples of various contents. Triaxial tests due to different percentage of cement from disturbed samples will be conducted in the laboratory. Soil Classification test was also performed on a disturbed samples. Samples were taken at Aur's River, Klang was identified as the soft clay soil samples. From the work, it was found that the use of cement stabilized or improved the strength of the soil especially when using the poor quality soil such as the 'soft clay'. The percentage increased in the ratio cement : soil sample, improved the soil properties from about 0% to 50%. However, the increase content of cement made by soil less workable